New pathways in the evaluation of programmes for men who perpetrate violence against their female partners. (August 2016) - Wojnicka, Katarzyna; Scambor, Christian; Kraus, Heinrich
Highlights: Programmes for male perpetrators of domestic violence. Evaluation of correction programmes. Outcome measurement. Multi/country, multi/side evaluation. Abstract: Today, evaluation research in the field of intervention programmes for men who perpetrate violence against their female partners still makes a fragmentary impression. Across Europe various evaluation studies have been performed. However, the methodologies applied are too heterogeneous to allow the combination of the results in a meta-analytical way. In this paper we propose a future pathway for organising outcome evaluation studies of domestic violence perpetrator programmes in community settings, so that today's problems in this field can be overcome. In a pragmatic framework that acknowledges the limited pre-conditions for evaluation studies in the area of domestic violence perpetrator programmes as it is today, feasible approaches for outcome evaluation are outlined, with recent developments in the field taken as starting points. The framework for organising future evaluation studies of work with perpetrators of domestic violence is presented together with a strategy to promote this framework. International networks of practitioners and researchers play a central role in this strategy through upskilling the area of practical work, preparing the ground for evaluation research and improving cooperation between practitioners and researchers. This paper is based on the results of the European funded project IMPACT (under the Daphne-III-funding programme of the European Commission).